Faktor-Faktor Yang Mempengaruhi Cash Holding - Garry, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study was conducted to examine the effect of liquidity, firm size, leverage and growth opportunity on corporate cash holding in listed manufacturing companies in Indonesian Stock Exchange (IDX) period 2016-2018. The sample used in this study is 75 manufacturing companies. This study used fixed effect model and multiple regression analysis. The results of this study indicate that liquidity has a significant positive effect on corporate cash holding, firm size has an insignificant negative effect on corporate cash holding, leverage has a significant positive effect on corporate cash holding, and growth opportunity has an insignificant negative effect on corporate cash holding